Trans Fatty Acids Suppress TNF‐α‐Induced Inflammatory Gene Expression in Endothelial (HUVEC) and Hepatocellular Carcinoma (HepG2) Cells. Issue 4 (18th March 2017) - Da Silva, Marine S.; Julien, Pierre; Bilodeau, Jean‐François; Barbier, Olivier; Rudkowska, Iwona
Abstract: Trans fatty acids (TFA) intake has been linked to cardiovascular diseases and liver diseases; yet the effect of TFA on inflammation remains controversial. Accordingly, the objective of this paper was to determine the in vitro effects of TFA on inflammatory gene expression. Human umbilical vein endothelial cells (HUVEC) and human hepatocellular carcinoma (HepG2) cells were treated for 24 h with either trans ‐vaccenic acid (tVA), trans ‐palmitoleic acid (tPA) or elaidic acid (EA) at concentrations of 5–150 µM, or with a mixture of tVA and tPA (150/50 µM). All TFA were highly incorporated into cell membranes, as determined by gas chromatography, representing 15–20% of total fatty acids in HUVEC and 3–8% in HepG2 cells. Incorporation of EA, a common industrial TFA, increased the ratio of the stearoyl‐CoA desaturase (SCD‐1), a key enzyme involved in fatty acid metabolism. Ruminant TFA, including tVA, tPA and the mixture of tVA and tPA, significantly reduced the TNF‐α‐induced gene expression of TNF, VCAM ‐ 1 and SOD2 in HUVEC, as well as TNF and IL ‐ 8 in HepG2 cells. EA also decreased inflammatory gene expression in HUVEC, but not in HepG2 cells. The inhibition of peroxisome proliferator‐activated receptor (PPAR)‐γ did not influence the effects of TFA on gene expression. Overall, physiological and supraphysiological concentrations of TFA, especially tVA and tPA, prevented inflammatory gene expression in vitro . This effect is independent of PPAR‐γ activation and may be due to an alteration of fatty acid metabolism in cell membranes caused by the high incorporation of TFA.